Herbal and Alternative Medicine Use in Tanzanian Adults Admitted with Hypertension-Related Diseases: A Mixed-Methods Study. (28th May 2017) - Liwa, Anthony; Roediger, Rebecca; Jaka, Hyasinta; Bougaila, Amina; Smart, Luke; Langwick, Stacey; Peck, Robert
Abstract : Background . Hypertension is increasingly common in sub-Saharan Africa where traditional medicine use is also common. We conducted a hospital-based, mixed-methods study to determine prevalence, pattern, and correlates of herbal and alternative medicine use in Tanzanian adults hospitalized with hypertension. Methods . A standardized questionnaire was administered. In-depth interviews were performed on a subset of participants. Factors associated with herbal medicine use were determined by logistic regression. The association between traditional medicine uses and allopathic medication adherence was determined using ordinal logistic regression. Qualitative data were analyzed according to grounded theory. Results . Of 213 adults enrolled, 52 (24.4%) reported using herbs during the previous month and 47 (22.1%) reported concurrent use of herbs and allopathic medicines. Lower educational level, nonprofessional employment, and lack of health insurance were significantly associated with herbal medicine use. Alternative medicines use was not associated with lower medication adherence. Qualitative interviews identified several important themes including reasons for herbal medicine use. Conclusion . The use of traditional medicines is very common among patients with hypertension. Adults from low socioeconomic status, those with misunderstandings about hypertension, and those without health insurance were more likely to take herbs. Open, nonjudgmental communication between healthcare workers and patients regarding use of traditional medicines must be encouraged in Africa.